Creating the image of political communicators with the use of social media and computer technology - Jankiewicz, Adam (Scripta Neophilologica Posnaniensia, 2020)
Nowadays, computer technology and social media can be used in certain ways to create positive or negative images of political communicators. More and more people receive political communication with the use of electronic devices via the Internet and social media. The ways in which one can create and transmit images of political communicators have evolved. Companies use new methods of gaining and delivering political information to receivers. At present, information technology is sometimes used not only to send political information but also to manipulate the receivers and change their political views in the fight for support and to win elections. Electronic devices, the Internet and social media, can be used to gain support or to defame political opponents. This paper has been written to bring closer how social media participation, computer technology and software can be utilized to obtain information which then, neatly tailored, can serve as a tool to manipulate political views of addressees of political communication. This article presents the procedure of obtaining, processing and applying information in creating images of politicians by private companies. It also analyzes people’s awareness of ways in which social media communication can be used in creation of political image. Hence, a survey has been conducted to research the participation of university students in social media and their awareness of how the data obtained from them can be used in for political reasons. The paper also explains how incorporating and combining social media platforms, psychology, algorithms, the Internet and cutting edge computer software opened new ways to impact political views with political communication.